When hope springs new [large type] - Oke, Janette, 1935- (Oke, Janette, 1935- Canadian West series, 2012)
Leaving behind their dear friends in Beaver Creek, Elizabeth and Wynn take over an even more primitive outpost in the Canadian Northwest.